UJI KONDUKTIVITAS TERMAL PADA DAUN BAYAM DENGAN MENGGUNAKAN THERMAL CONDUCTIVITY APPARATUS - Firmansyah, Firmansyah; Syafutra, Heriyanto; Sidikrubadi, Sidikrubadi; Irzaman, Irzaman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Abstract Has successfully tested thermal conductivity on spinach leaves by using Thermal Conductivity Apparatus. Thermal conductivity Apparatus assisted with Steam generator, Caliper, Micrometer, and iron. The thermal conductivity value of spinach leaves is 0.5208 watts / (m.K). This thermal conductivity test on foliage, fruits using Thermal Conductivity Apparatus are very easy to do in Basic Physics Laboratory by physics study program students in Indonesia. Keywords: Thermal Conductivity, Leaf spinach, Thermal Conductivity Apparatus, watt/(m.K).